(untitled) (Biological Sciences - PJSIR, 1994)
The seeds (200 g) of A. squamosa were crushed in an elec- tric grinder and then extracted with hexane ina Soxhlet extrac- tor. The solvent was removed under reduced pressure toafford 31 g of liquid oil which was saponified and methyl esters prepared by usual procedure.